Maps of meaning : the architecture of belief - Peterson, Jordan B. (New York : Routledge, 1999)
"Why would people in different places and times formulate myths and stories with similar symbols and meanings? Are groups of people with different religious or ideological beliefs doomed to eternal conflict? Are the claims of science and religion truly irreconcilable? What might be done to decrease the individual propensity for group-fostered cruelty? Maps of Meaning addresses these questions with a provocative new hypothesis that explores the connection between what modern neuropsychology tells us about the brain and what rituals, myths and religious stories have long narrated. Peterson's ambitious interdisciplinary odyssey draws insights from the worlds of religion, cognitive science and Jungian approaches to mythology and narrative. Maps of Meaning offers a critical guide to the riches of archaic and modern thought and invaluable insights into human motivation and emotion."
Includes bibliographical references and index.
Keywords: Archetype (Psychology).; Meaning (Psychology).